High temperature cathodic protection of Fe-Cr alloy - Ani, Mohd Hanafi; Azman, M. A. F.; Musa, Mukhtaruddin; Anhar, Zaki; Abdul Hamid, Abd. Malek (IOP Publishing Ltd, 2020)
Power plant industry extensively using ferritic Fe-Cr alloys as boiler materials due to its good resistant to creep, low in thermal shock and thermal expansion. However, the development of new generation of Ultra Supercritical (USC) power plant requires boiler materials to be operate at higher temperature and pressure, thus make it susceptible to high temperature oxidation. The USC power plant successfully reaching the target of working temperature at temperature more than 873K (600°C). By increasing the operating temperature, the efficiency of power plant also increases at the expense of acceleration of high temperature oxidation. This project explored the application of impressed current cathidic protection (ICCP) at 1073 K. At high temperature, gas may dissociates into charged ions that make it possible to conduct electrons. Typical boiler material of T91 was used in high temperature oxidation at 1073K, under Ar-20%O2 mixed gas. The sample is connected to potentiostat with Pt wire to measure the value of corrosion potential (Ecorr), and Icorr. Blank experiment is conducted to determine the presence of reaction by the presence of current conductivity at high temperature in oxygen condition. The weight gain is following parabolic’s rate law, which shows that diffusion is the rate determing step. Blank test shows that as potential induced, current flows from one Pt terminal to another Pt terminal through intermediate mixed gas. Corrosion potential (Ecorr) of the sample show the value is greater than value at room temperature. It is concluded that ICCP is feasible to be conducted for controlling corrosion at high temperature.